PENGARUH KETELADANAN ORANG TUA TERHADAP PEMBENTUKAN KARAKTER RELIGIUS SISWA DI SMK HASYIM ASY'ARI PUCUK LAMONGAN - Devi Putri Nurul Izzah; Mahbub Junaidi; Zuli Dwi Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of parental role models on the formation of students' religious character at Hasyim Asy'ari Vocational High School, Pucuk District, Lamongan Regency. This study uses a quantitative approach with a simple linear regression method. The study population was 83 students, while the sample was 69 students determined using the Slovin formula. Data collection methods were carried out through questionnaires, observation, and participation. The research instrument has undergone validity and reliability tests using IBM SPSS operations. The results of the validity test show that all specific statements have a significance value of 0.05. Simple linear regression analysis produces the equation Y = 20.770 + 0.698 X which indicates a positive influence between parental role models on students' religious character. The t-test results reached a significance value of 0.000 <0.05, therefore H1 is accepted. The coefficient of determination (R²) value of 0.547 indicates that parental role models contribute 54.7% to the formation of students' religious character, while the rest is influenced by other factors outside the study. The findings of this study emphasize the importance of parental role models in shaping students' religious character through the application of religious values ​​in everyday life.